(3eMGce GdJaJjT YHQ GdJGQjNs - (3YHO GdMcje, efUhQs ((3GdLjRI, eUQs (3OGQ GdaGQhb ddGSJKeGQGJ GdKbGajIs, 2022)
(3de jTgO GdJGQjN GdEfSGfj eMGce CShC ef eMGce GdJaJjT GdJj XgQJ aj cKjQ ef GdbGQI GdChQHjI Ke EfJbdJ Edi CeQjcG GdLfhHjI, dMhGdj ef SHYI Ch KeGfjI bQhf, cGfJ Jdc GdeMGce HeKGjI MQhH UdjHjI Ydi CJHGY GdOjf GdeSjMj (B((3GdcGKhdjc (B)(3dGJgGege HGdgQGWbI aj ChQHG h CeQjcG GdLfhHjI, agj eMGceGJ OjfjI hePgHjI hSjGSjI (B. (3jCNOfG GdeDda QMdI SfHMQ ajgG ekYG YHQ GdJGQjN, dfYQa JGQjN Jdc GdeMGce GdJj JYO CShC eMGce YQaJgG GdHTQjI, hCjf hLOJ Jdc GdeMGce aj ChQHG ? hef ge GdPjf MGceJge ? hgd MbbJ CgOGagG GdJj CfTFJ ef CLdgG ? hef ge CTgQ ef GcJnhhG HfjQGfgG? h eGgj CSGdjH hhSGFd Jdc GdeMGceGJ GdJj CXgQJ HTGYJgG ?s
Keywords: (3GdYUhQ GdhSWis -- (3JGQjNs; (3GdeMGces -- (3QheGs; (3MVGQI GdYUhQ GdhSWis; (3eMGce GdJaJjTs